Login
Remember
Register
Home
All Activity
Q&A
Questions
Hot!
Unanswered
Tags
Categories
Users
Ask a Question
Ask a Question
`[2^(–1) + 3^(–1) + 4^(–1)]^0` =
0
votes
asked
Jan 17, 2022
in
8th-maths
by
yogita
(
1.8k
points)
`[2^(–1) + 3^(–1) + 4^(–1)]^0` = ______
marks1
chapter8
#fib
Please
log in
or
register
to answer this question.
0
Answers
Categories
All categories
Maths
(8.6k)
12th-maths
(0)
11th-maths
(0)
10th maths
(0)
9th-maths
(0)
8th-maths
(8.6k)
Science
(14)
Physics
(3.4k)
Related questions
`[2^(–1) + 3^(–1) + 4^(–1)]^0` =
`[2^(–1) + 3^(–1) + 4^(–1)]^0` =
`[2^(–1) + 3^(–1) + 4^(–1)]^0` =
`[2^(–1) + 3^(–1) + 4^(–1)]^0` =
`[2^(–1) + 3^(–1) + 4^(–1)]^0` =